Ответы и объяснения

Лучший Ответ!
2011-12-16T13:47:00+00:00

(sinx+sin5x)+sin3x=0

2sin[(x+5x)/2]* cos[(x-5x)/2] + sin3x=0

2sin(6x/2) * cos(-4x/2)+sin3x=0

2sin3x * cos2x + sin3x=0

sin3x* (2cos2x+1)=0

sin3x=0                     2cos2x+1=0

3x=2pi*k, k∈(-∞;+∞)        2cos2x=-1

x=2/3 pi*k, k∈(-∞;+∞)       cos2x=-1/2

                                      2x=pi- arccos(1/2)

                                       2x= pi- pi/3 +pi*k,        k∈(-∞;+∞)

                                       2x= 2pi/3 + pi*k, k∈(-∞;+∞)

                                         x= pi/3 + pi/2 *k,   k∈(-∞;+∞)